Polyneuropathie und Enzephalopathie durch organische Lösungsmittel und Lösungsmittelgemische Arbeitsmedizinische und neurologische Aspekte zur neuen Berufskrankheit - Triebig, Gerhard; Grobe, Thomas G.; Dietz, Michael Christof (Der Nervenarzt, 1999)
SummarySolvent induced polyneuropathy and encephalopathy have been acknowledged quite recently as occupational diseases in Germany. For compensation first of all the diagnosis has to be proven. For differential diagnosis other known causes as well as non-organic mental diseases must be taken into consideration. The causality between proven exposures and diagnosed disease has at least to be probable. To evaluate causation extensive experience of the experts is needed. In this context scientific criteria regarding neurotoxicity of the solvent, duration of exposure, individual aspects of non-occupational influences, time course of the disease are important within a thorough synoptic evaluation. Possibilities and limitations of sensitive diagnostic measures such as neurographic, neuropsychologic and neuroimaging examinations are discussed. The prognosis of toxic polyneuropathy and encephalopathy is in general favorable if exposure has stopped. Additionally, adequate therapy and rehabilitation measures are supportive for a good prognosis.
Gesehen am 23.10.2017